Demographic profile of Cervical Cancer development: a hospital based study - Chandana Ray Das; Manab Deka; Sujoy Bose; Purabi Deka Bose; Gokul Ch Das (International Journal of Medical Research and Review, 2014)
Introduction: The present study is an attempt to detect Human papilloma virus infection along with its genotype in cancer cervix and its relation with demographic profile.Methods: Cervical cancer cases were enrolled in between Jan’ 2010 to Dec’ 2012. One sample was collected from non cancerous area of cervix for DNA extraction and two samples were collected from cancerous area of cervix from same patient, one for DNA extraction and other one for histopathological examination to confirm our clinical diagnosis. Extracted DNA was then checked for presence of HPV DNA by PCR amplification method using MY09/11 primer. HPV genotyping was done by using specific primer for HPV16 & HPV18. The cases were compared with their corresponding socio demographic profile.Results: The study showed 88.88% cases found to be HPV positive in cancerous area compared to 7.4% number in non cancerous area. Out of which 95.83% cases to be HPV 16 and only 4.16% were to be HPV 18 in cervical cancer cases. There were other significant risk factor association of cervical cancer with early marriage in 70.36% and high parity 87% of cases.Conclusion: The human papilloma virus type 16 & 18 are the major contributing factor along with other risk factors like early marriage, illiteracy and high parity for cervical cancer in our region.